2021
DOI: 10.20945/2359-3997000000334
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a glucose meter connected to a mobile app on glycemic control and adherence to self-care tasks in patients with T1DM and LADA: a parallel-group, open-label, clinical treatment trial

Abstract: Objective: The main aim of the study was to evaluate the patients' glycemic control and adherence to self-care tasks. Materials and methods: Patients with type 1 diabetes mellitus (T1DM) or latent autoimmune diabetes of the adult (LADA) using a multiple daily injection (MDI) regimen with carbohydrate counting (n = 25, Subgroup B) or fixed insulin dose (n = 25, Subgroup C) were allocated to use the application (app) for 12 weeks. Both subgroups were compared with each other and against a control group (n = 25, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As for the use of apps and the food scale, using specific and non-specific CC apps and using the food scale to do the CC, when eating something different than usual and to make culinary recipes was associated with having adequate HbA1c in this study. Using mobile apps and food scales helps to perform CC more accurately and frequently, optimizing glycemic control and reducing counting errors ( 49 51 ). In the cross-sectional study by Trawley et al.…”
Section: Discussionmentioning
confidence: 99%
“…As for the use of apps and the food scale, using specific and non-specific CC apps and using the food scale to do the CC, when eating something different than usual and to make culinary recipes was associated with having adequate HbA1c in this study. Using mobile apps and food scales helps to perform CC more accurately and frequently, optimizing glycemic control and reducing counting errors ( 49 51 ). In the cross-sectional study by Trawley et al.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review and meta-analysis of efficacy of mobile APPs to support care of people with diabetes, confirmed that A1c could be improved when it strengthens the perception of self-care and allow remote access to health care professional, but an important characteristic measured in these studies was participants education degree and the ability in adopting new technologies [ 25 ]. In addition, a recent Brazilian study carried out with a group of adults with T1D or latent autoimmune diabetes of adult (LADA), undergoing treatment with MDI plus carbohydrate counts or MDI plus fixed doses of insulin compared to CSII also observed that using SMBG device connected to a cell phone application contributed to better glycemic control and increased adherence to tasks of self-care [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some apps are designed for the general population and may present challenges for those with health conditions, there are also apps that are specifically helpful for managing certain conditions like T1DM. For instance, diabetes apps have shown benefits for glycemic control ( 20 ), reducing HbA1c ( 21 ), and improving health-related quality of life (HRQL) ( 22 ).…”
Section: Introductionmentioning
confidence: 99%